Effect Of Giving Virgin Coconut Oil And Physical Exercise On Leukocyte Levels In Non-Athlete Students - Rika Nailuvar Sinaga; Fajar Apollo Sinaga; Ayu Elvana (CV. Inara, 2024)
In recent years there has been an increase in the prevalence of viral infections worldwide with the outbreak of the Coronavirus Disease. Various attempts have been made to find new drugs and vaccines against the viruses that cause it, but there are no effective preventive and curative drugs yet, so boosting the immune system is one of the most important things to do. One of the natural ingredients that are believed to increase the body's immunity is Virgin Coconut Oil (VCO), but it still needs more intense research. In addition to the use of natural ingredients, exercise is also important to maintain and increase immunity. One indicator that is sensitive to impaired immune response is leukocytes. This study aims to see the effect of giving VCO and physical exercise on immune function by measuring leukocyte levels. This is an experimental study with a randomized control group pretest-posttest design. The sample in this study were 12 people who were divided into two groups. During the exercise with an intensity of 70-80% in two weeks with a frequency of three times a week, the experimental group was given 15 ml of VCO every day while the control group was given a placebo. Leukocyte levels were measured before and after treatment. Leukocyte levels in the control group increased significantly while the experimental group decreased insignificantly. Giving virgin coconut oil in this study significantly reduced leukocyte levels.